Pemberdayaan Objek Wisata Bukit Widodaren Desa Sendang Ijo Kecamatan Selogiri Kabupaten Wonogiri - VIRGIAWAN, SENNA; Herawati, Augustin Rina; Dwimawanti, Ida Hayu (Amalee: Indonesian Journal of Community Research and Engagement, 2022)
This mentoring aims to discuss empowerment activities carried out on the Widodaren hill, Sendang Ijo Village, Selogiri District, Wonogiri Regency. The mentoring method uses an asset-based community development (ABCD) approach. Based on the results of the first stage of assistance is to identify individual assets and institutional associations that make up the community. The second stage is to equate the interests or needs of these advantages. The third stage in the development of Widodaren hill tourism is to form associations and organizations that actively manage Widodaren hill to become tourism. The results of the assistance found that the empowerment of the Widodaren Hill tourist attraction was carried out in stages because it required coordination of interested parties in the community so that it became a superior tour. This means that the construction of the Widodaren hill has an impact on economic development for the community. Pendampingan ini bertujuan untuk membahas kegiatan pemberdayaan yang dilakukan di bukit Widodaren Desa Sendang Ijo Kecamatan Selogiri Kabupaten Wonogiri. Metode pendampingan menggunakan pendekatan pengembangan masyarakat berbasis aset (ABCD). Berdasarkan hasil pendampingan tahap pertama adalah mengidentifikasi aset individu dan asosiasi institusional yang membentuk komunitas. Tahap kedua adalah dicocokkan menyamakan kepentingan atau kebutuhan akan kelebihan tersebut. Tahap ketiga dalam pengembangan wisata bukit Widodaren dibentuk paguyuban dan organisasi yang secara aktif mengelola bukit Widodaren menjadi wisata. Hasil pendampingan didapatkan bahwa pemberdayaan objek wisata Bukit Widodaren dilakukan secara bertahap karena membutuhkan koordinasi pihak-pihak yang berkepentingan dalam masyarakat agar menjadi wisata yang unggul. Dengan demikian disimpulkan bahwa pengembangan bukit Widodaren memberikan dampak pengembangan ekonomi bagi masyarakat.